2022
DOI: 10.18608/jla.2022.7669
|View full text |Cite
|
Sign up to set email alerts
|

Networks and Learning: A View from Physics

Abstract: Like learning analytics, physics education research is a relatively young field that draws on perspectives from multiple disciplines. Network analysis has an even more heterodox perspective, with roots in mathematics, sociology, and, more recently, computer science and physics. This paper reviews how network analysis has been used in physics education research and how it connects to some of the work in this special issue. Insights from physics education research suggest combining social and interaction network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…For the nodal variables, we focused on degree (the number of adjacent edges connected to a node), rather than other measures of centrality (such as closeness and betweenness). Degree is simple to interpret and prior research has shown that degree both sufficiently captures network structure and is useful in predicting students' learning outcomes [46,47]. Our final model, which we applied using the 'ergm' package in the statistical software R [45] and the input variables listed in parentheses below, included the following predictor variables:…”
Section: Discussionmentioning
confidence: 99%
“…For the nodal variables, we focused on degree (the number of adjacent edges connected to a node), rather than other measures of centrality (such as closeness and betweenness). Degree is simple to interpret and prior research has shown that degree both sufficiently captures network structure and is useful in predicting students' learning outcomes [46,47]. Our final model, which we applied using the 'ergm' package in the statistical software R [45] and the input variables listed in parentheses below, included the following predictor variables:…”
Section: Discussionmentioning
confidence: 99%
“…La présente recherche met en évidence la nature interdisciplinaire des sciences physiques en impliquant d'autre composante tels que les mathématiques, l'environnement, la sociologie et l'informatique [12]. Alors, l'engagement des apprenants dans les sciences, y compris les sciences physiques, est influencé par leur compréhension de la matière et leurs expériences informelles [13].…”
Section: Discussionunclassified
“…During the training, network modeling is also applied. Interdisciplinary dependencies are established between results and analyses in the natural sciences (Ignatov, 1989;Traxler, 2022). Iliev takes part in educational project BG051PO001-3.3.07-0001 "SCHOOL PRACTICE with the financial support of the Operational Program "Development of Human Resources," financed by the European Social Fund of the European Union, a project of the Ministry of Education and Science -Bulgaria.…”
Section: Educational Practices and Specializationsmentioning
confidence: 99%